(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The proliferation of Internet of Things (IoT) devices has led to unprecedented connectivity and convenience in various domains. However, the dynamic and heterogeneous nature of IoT environments presents significant security challenges. Traditional security mechanisms often fall short in addressing these challenges effectively. In response, attribute-based security techniques have emerged as a promising approach to enhance the security posture of IoT devices. This review paper provides a comprehensive analysis of attribute-based security techniques in IoT devices, including their principles, implementation strategies, case studies, challenges, and future directions. By synthesizing existing research findings and best practices, this paper aims to provide insights and guidelines for designing and deploying effective attribute-based security solutions in IoT environments.